STRATEGI KIKI SULISTYO DALAM ARENA SASTRA INDONESIA - Dharma Satrya HD (Universitas Sebelas Maret, 2018)
This paper discusses Kiki Sulistyo’s strategy for reaching position in Indonesia literary field. This research applied phenomenology and structural analysis method. Data were gathered by interview and objectification from social structure. The style of the writers’ poems and his consciousness toward Lombok were analyzed by phenomenology. The research result shows that Lombok literary field is denoted as the economy upside. Kiki Sulistyo denounces the world economy, thus moving within the production of a restricted arena. Kiki Sulistyo created literature as a movement, so he formed Akar Pohon community. Through this community, he generates a young poet and simultaneously undertakes a project of publishing works. Two anthologies of poetry he published brought him to the position of a legitimate poet. The legitimacy is given by poets, literary scholars, and institutions